2008
DOI: 10.1243/09544054jem838
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and bending behaviour of metal foils

Abstract: Ongoing miniaturization in various technical fields such as the electronics industry or micro-systems technology requires precise forming processes for the production of small and thin components; for example, thin metal foils are being used in microelectromechanical systems, electronic components, and medical devices. In the same manner as micro bulk-metal-forming processes, metal foils with thicknesses in the range of microns are subjected to so-called size effects. Previous investigations of various metal-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…First and second order derivatives in Eq. (10)are calculated at the midpoint of the deformable region.…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…First and second order derivatives in Eq. (10)are calculated at the midpoint of the deformable region.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…It is not only dependent on the thickness of the sheet but also influenced by parameters like grain size, number of grains across the thickness direction, crystal orientation with respect to loading direction etc. [22,16,10,28,45,15,23]. This complexity in size effect makes it difficult to transfer the knowledge (theoretical and practical) of conventional forming operation directly to the micro-forming operation.…”
Section: Introductionmentioning
confidence: 99%
“…The interactive effect of grain and specimen sizes are investigated on the flow stress of sheet metal in microforming via the tensile test of pure copper and numerical modeling . In micro‐bending process, the grain size and thickness of sheet metal, especially for the ratio of sheet metal thickness t to grain size d , are the key factors affecting bending force and springback angle . To extensively investigate the size effect in microforming processes, different material constitutive models were proposed to explain the relationship between the deformation behavior of materials and grain size.…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed a constitutive model based on the surface layer model to study the materials' mechanical response, and linked it with springback behaviour. Diehl et al [18] performed free bending test to find that the scatter of springback angles in coarse-grained material was greater than that in the fine-grained one. [9]Recently, increasing numbers of research are focusing on the grain structure [19] and grains' stress-strain state [20,21] to explain the correlation between the grain size effect and springback.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [11,16,18] have proved that the ratio T/D is a wide-applied indicator evaluation parameter for studying the relationship between the the grain size effect and springback. However, it is also found that there is a lack of research on grain size effect when the ratio is around 1 (greater than 1, less than 1 and equal to 1).…”
Section: Introductionmentioning
confidence: 99%